Optimal plot size for cabbage experiments (Research, Society and Development, 2020)
Among the factors that influence the detection of minimum significant differences between treatments in conventional experiments is the size of the plot, whose correct determination allows the reduction of experimental error, consequently, increases the precision of the experiment and the reliability of the interpretations and conclusions obtained. There are different methods to estimate the optimal plot size, which relate plot size and residual variation, highlighting among these the methods of maximum curvature, maximum modified curvature, maximum curvature of the coefficient of variation and regression with plateau response. In addition to these, there is the Hatheway method that takes into account factors such as number of treatments, repetitions and levels of significance. Since there is little work to estimate the optimal plot size in experiments with species of the genus Brassica, the present study aimed to increase the experimental precision in experiments with cabbage in the municipality of Alegre - ES by determining the optimal plot size with based on Hatheway's methods, maximum curvature, maximum curvature of the coefficient of variation and plateau regression. The work was carried out by means of a blank test carried out in the experimental area of the Center for Agricultural Sciences of the Federal University of Espírito Santo, Alegre - ES, in which both productive and growth variables were evaluated. At the end of the project, propose the optimal plot size to be used in experiments with cabbage in order to increase the experimental precision and the reliability of the results obtained in future experiments.